Child Labor : Lessons from the Historical Experience of Today's Industrial Economies - Humphries, Janes (Washington, DC: World Bank, 2014)
Child labor was more prevalent in 19th-century industrializers than it is in developing countries today. It was particularly extensive in the earliest industrializers. This pattern may be a source of optimism signaling the spread of technologies that have little use for child labor and of values that endorse the preservation and protection of childhood. Today and historically, orphaned and fatherless children and those in large families are most vulnerable. Efficient interventions to curb child labor involve fiscal transfers to these children and active policies toward street children. Changes in capitalist labor markets (including technology), family strategies, state policies, and cultural norms are examined to shed light on the causes, chronology, and consequences of child labor.